Exploring perceptions of health literacy, healthcare access, and utilisation among higher education students in Alentejo, Southern Portugal: A qualitative study. - Jorge Rosário; Joana Correia Pires; Sónia Dias; Ana Rita Pedro (PLoS ONE, 2025)
Introduction Health Literacy (HL), defined as the ability to access, understand, appraise and apply health information to make informed decisions, is essential for individual and public health. However, in rural regions such as Alentejo, Portugal, higher education students often encounter specific challenges that hinder the development and effective use of these skills. This study aimed to explore the perceptions of higher education students in Alentejo, Portugal, with regard to health literacy, access to and utilisation of healthcare, and to identify barriers, facilitators and interventions to inform strategies that promote equity, build student capacity and sustainably improve health outcomes. Methodology A qualitative, exploratory, and descriptive study was conducted using three focus groups held on 11th, 13th, and 18th December 2023, with a purposive non-probability sample of 29 participants across first-year, intermediate, and final-year levels. The participants shared their experiences, challenges, and resources related to health literacy, healthcare access, and utilisation. The focus group discussions were audio-recorded, transcribed verbatim, and analysed through a systematic process of open, axial, and selective coding. Codes were organised into categories, and thematic identification was facilitated using a constant comparative method. Content analysis was conducted with MAXQDA® 22 software. Ethical approval was obtained from the Ethics Committee of the University of Évora, Portugal, and informed consent was secured from all participants. Results The students' perception was that health literacy, access to and utilisation of healthcare are influenced by a dynamic interaction of barriers and facilitators. The identified barriers encompassed the presence of misinformation, financial and logistical challenges, and emotional stigma, particularly in the context of mental and sexual health. Conversely, facilitators were identified as encompassing access to digital tools, a family and peer support network, professional guidance and institutional resources such as libraries and workshops. The students recommended that interventions to improve health literacy be integrated into the higher education curriculum, that navigation support systems be improved and that structural inequalities be explored in order to improve access to and participation in healthcare. Conclusion Digital resources have the potential to improve access to health information; however, persistent challenges such as misinformation, financial constraints and stigma limit their impact. This study underscores the significance of specific interventions to enhance health literacy and healthcare navigation skills. These interventions include the integration of health literacy into academic curricula, the provision of specialised workshops, and the facilitation of access to healthcare services. The study identifies nursing interventions and institutional support as key strategies to promote equitable access to healthcare and improve student wellbeing.